Fragile-X Syndrome Is Associated With NMDA Receptor Hypofunction and Reduced Dendritic Complexity in Mature Dentate Granule Cells - Yau, Suk-Yu; Bettio, Luis; Chiu, Jason; Chiu, Christine; Christie, Brian R. (Frontiers in Molecular Neuroscience, 2019)
Fragile X Syndrome (FXS) is the most common form of inherited intellectual disability. It is caused by the overexpansion of cytosine-guanine-guanine (CGG) trinucleotide in Fmr1 gene, resulting in complete loss of the Fragile X Mental Retardation Protein (FMRP). Previous studies using Fmr1 knockout (Fmr1 KO) mice have suggested that a N-methyl-D-aspartate receptors (NMDAR) hypofunction in the hippocampal dentate gyrus may partly contribute to cognitive impairments in FXS. Since activation of NMDAR plays an important role in dendritic arborization during neuronal development, we examined whether deficits in NMDAR function are associated with alterations in dendritic complexity in the hippocampal dentate region. The dentate granule cell layer (GCL) presents active postnatal neurogenesis, and consists of a heterogenous neuronal population with gradient ages from the superficial to its deep layer. Here we show that neurons with multiple primary dendrites that reside in the outer GCL of Fmr1 KO mice display significantly smaller NMDAR excitatory postsynaptic currents (EPSCs) and a higher α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) to NMDA ratio in comparison to their wild-type counterparts. These deficits were associated with a significant decrease in dendritic complexity, with both dendritic length and number of intersections being significantly reduced. In contrast, although neurons with a single primary dendrite resided in the inner GCL of Fmr1 KO mice had a trend towards a reduction in NMDAR EPSCs and a higher AMPA/NMDA ratio, no alterations were found in dendritic complexity at this developmental stage. Our data indicate that the loss of FMRP causes NMDAR deficits and reduced dendritic complexity in granule neurons with multiple primary dendrites which are thought to be more mature in the GCL.